Spinal Structure of Mice Fetus (Mus musculus L.) Treated by Acanthus ilicifolius L. Leaves Extract - Tunggul Van Roy; Nuning Nurcahyani; Sutyarso Sutyarso; Hendri Busman (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2019)
Jeruju had various chemical components. This study was conducted on the teratogenic test of jeruju leaf extract to determine abnormalities in fetal mice (Mus musculus L.). This study used a completely randomized design (CRD) method with 20 pregnant female mice divided into 4 groups: 1 group as a control and 3 groups treated with a dose of 3.75 mg/30grBB, 7.5 mg/30grBB, 15 mg/grBB, each with jeruju leaf extract consists of 5 repetitions. The results showed that the doses of 7.5 mg/30grBB and 15 mg/grBB significantly decreased fetal weight and length when compared with controls. This is suspected because there is an active substance in the jeruju leaf extract which is cytotoxic. Anatomically the administration of jeruju leaf extract does not cause abnormalities in the structure of the fetal spine of mice. This is due to the growing fetus taking priority from the many types of nutrients in the mother fluid so that the fetal bone can continue to grow and develop.